Economic Recovery But Stagnating Mental Health During A Global Pandemic? Evidence From Ghana And South Africa - Durizzo, K.; Asiedu, E.; Merwe, A.V.D.; Günther, I. (Review of Income and Wealth, 2022)
Ghana and South Africa proactively implemented lockdowns very early in the pandemic. We analyze a three-wave panel of households in Accra and Greater Johannesburg to study the mental and economic well-being of the urban poor between the COVID-19 lockdown and the “new normal” one year later. We find that even if economic well-being has mostly recovered, life satisfaction has only improved slightly and feelings of depression are again at lockdown levels one year into the pandemic. While economic factors are strongly correlated with mental health and explain the differences in mental health between South Africa and Ghana, increasing worries about the future and limited knowledge about the pandemic (both countries), as well as deteriorating physical health (South Africa) and trust in government (Ghana) explain why mental health has not recovered. Therefore, we need broad and country-specific policies. beyond financial support, to accelerate the post-pandemic recovery of the urban poor
Research Article
Keywords: COVID-19; economic recovery; mental health